2007
DOI: 10.1055/s-2007-964989
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physical Fitness and Throwing Velocity Among Elite and Amateur Female Handball Players

Abstract: This study compared physical characteristics (body height [BH], body mass [BM], body fat [BF], and fat free mass [FFM]), one repetition maximum bench press (1RM (BP)), jumping explosive power (VJ), handball throwing velocity, power-load relationship of the leg and arm extensor muscles, 5- and 15-m sprint running time, and running endurance in elite (n = 16; EF) and amateur (n = 15; AF) female handball players aged 17 - 38. Results revealed that, compared to AF, EF players presented similar values in body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
133
5
22

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 24 publications
(52 reference statements)
12
133
5
22
Order By: Relevance
“…The power of the lower extremity and the maximal running speed, as expressed by standing long jump and 30-meter speed, respectively, had a significant correlation with ball throwing velocity. The former association has been also reported in high level handball male and female players [20]. Our data are also in accordance with a study of volleyball players which reports a significant correlation between vertical jump and ball velocity during spiking [17] and with another study which reported a correlation between squat jump performance and medicine ball throwing velocity [21].…”
Section: Physical Fitness Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…The power of the lower extremity and the maximal running speed, as expressed by standing long jump and 30-meter speed, respectively, had a significant correlation with ball throwing velocity. The former association has been also reported in high level handball male and female players [20]. Our data are also in accordance with a study of volleyball players which reports a significant correlation between vertical jump and ball velocity during spiking [17] and with another study which reported a correlation between squat jump performance and medicine ball throwing velocity [21].…”
Section: Physical Fitness Characteristicssupporting
confidence: 93%
“…Running speed and explosive power are important prerequisite factors in competitive handball [19,20]. The power of the lower extremity and the maximal running speed, as expressed by standing long jump and 30-meter speed, respectively, had a significant correlation with ball throwing velocity.…”
Section: Physical Fitness Characteristicsmentioning
confidence: 99%
“…Los valores de altura del grupo de las jugadoras sénior tanto del equipo A como la B se encuentran próximos a los resultados del estudio de Granados et al (2007) Hlatky et al (1993). Los resultados del peso obtenidos por Sánchez et al (2007) y Vila et al (2007 (56,6 ± 5,3 kg y 64,8 ± 10,4 kg respectivamente) en jugadoras de categoría juvenil son inferiores a los resultados del presente estudio (70,4 ± 12,1 kg).…”
Section: Discussionunclassified
“…Según Wallace y Cardinale (1977) las exigencias físicas predominantes en este deporte son la resistencia aeróbica para permitir mejores recuperaciones en un deporte de carácter intermitente, la fuerza explosiva de los miembros superiores e inferiores para conseguir altas velocidades de desplazamiento y lanzamiento, la fuerza máxima y la potencia necesaria en las acciones de contacto contra los adversarios. Todas estas capacidades físicas son importantes para contribuir al alto rendimiento del equipo (Gorostiaga, Ibáñez, Ruesta, Granados e Izquierdo, 2009;Granados, Izquierdo, Ibáñez, Bonnabau y Gorostiaga, 2007;Vilkas, Tubelis y Dadelene, 2005;Zapartidis, Toganidis, Vareltzis, Christodoulidis, Kororos y Skoufas, 2009 De las habilidades motoras específicas mencionadas anteriormente, el lanzamiento es una caracterís-tica fundamental en el balonmano (Fleck et al, 1992;Gorostiaga,Granados, Ibáñez e Izquierdo, 2005;Granados et al, 2007;Granados, Izquierdo, Ibáñez, Ruesta y Gorostiaga, 2008;Marqués, Van Den Tilaar, Vescovi y González-Badillo, 2007;Skoufas, Kotzamanidis, Hatzikotoylas, Bebetsos y Patikas, 2003;Van Den Tilaar, 2004;Van Den Tillar y Ettema, 2003). Los estudios señalan que la magnitud de la velocidad del lanzamiento depende no sólo de la fuerza muscular, sino también de otros factores como la coordinación de diferentes segmentos corporales (Van Muijen, Joiris, Kemper y Van Ingen Schenau, 1991), ya que cuanto más rápido y preciso se lanza el balón, más difícil es poder interceptarlo para los defensas y porteros.…”
Section: Introductionunclassified
“…Handball players require to have well developed aerobic and anaerobic capacities to excel the performance (Delamarce et al, 1987;Gorostiaga et al, 2006). Several motor abilities such as jumping, sprinting, throwing velocity and flexibility are considered as important aspects of the players for the maximal performance (Marczinka, 1993;Marques and Gonzalez-Badillo, 2006;Granados et al, 2007). Under the acute competitive conditions, specific anthropometric characteristics play an important role for the excellent performance of the players (Srhoj et al, 2002;Zaportidis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%